A sensitive competitive enzyme immunoassay for detection of erythrosine in foodstuffs. (January 2015) - Xu, Zhihuan; Zheng, Lei; Yin, Yongmei; Wang, Jing; Wang, Peng; Ren, Linlin; Eremin, Sergei A.; He, Xiaodan; Meng, Meng; Xi, Rimo
Abstract: An enzyme immunoassay for erythrosine (Ery) in food products was developed in this study. Anti-Ery polyclonal antibody was obtained by immunizing rabbits with Ery-cationized BSA (cBSA) conjugates. Coupling ratios of erythrosine to carrier proteins were measured to be 16.6:1 in immunogen and 13.5:1 in coating antigen. The developed method showed high sensitivity with the IC50 value up to 29.1 ± 6.79 ng mL −1 . In food samples (healthy energy drink, breezer, grape juice, coca-cola sugar, fermented bean curd and tomato paste), the limit of detection (LOD) values of the developed method ranged from 2.2 ng mL −1 to 8.3 ng mL −1 . The recoveries ranged from 86.3% to 115.5%. Intra-assay and inter-assay variation were lower than 9.6% and 10.7% respectively. The method could specifically recognize Ery among commonly used food colors, and the results obtained with the proposed immunoassay were well related with that of the reference high performance liquid chromatography ( R 2 > 0.9999). Therefore, the proposed method could be selectively used for rapid screening Ery in the mentioned foodstuffs. Highlights: A polyclonal antibody for erythrosine was produced. An indirect competitive enzyme-linked immunosorbent assay for erythrosine is developed. The method shows good sensitivity and accuracy when applied in six kinds of foods. The method is more sensitive than traditional HPLC method.